Calibration and verification of century based wave climate data record along the Turkish coasts using satellite altimeter data. Issue 10 (15th November 2020) - Oztunali Ozbahceci, B.; Turgut, A.R.; Bozoklu, A.; Abdalla, S.
Abstract: In order to produce consistent reanalysis of the climate system, ECMWF (The European Centre for Medium-Range Weather Forecasts) has produced firstly an uncoupled atmospheric reanalysis ERA-20C, and then a coupled climate reanalysis, called CERA-20C, which covers the period January 1900 to December 2010. Both data sets are available at 3-hour time increments. Such a century long data can be an alternative to calculate the extreme waves corresponding to low probability of occurrences without extrapolation of extreme value statistics' results which may contribute to the error in the estimation of design waves in case of small number of wave data. In this study, main purpose is to calibrate and verify the century-based wave data in order to derive the longest and the consistent wave data along the Turkish coasts as a first time to be used in the extreme wave analysis. For this purpose, first of all, significant wave height data of ERA-20C and CERA-20C are compared by using ENVISAT data over the whole Black Sea for 2007–2008 as a pilot study. Comparison results show that both datasets give similar results but CERA-20C seems to be better in terms of statistical error measures. Then CERA-20C significant wave height data are calibrated using satellite Radar Altimeter data set. Jason family of satellites (TOPEX, Jason-1 and 2) and Envisat family of satellites (ERS-2 and Envisat) are inter-calibrated to get the consistent satellite data sets with a total duration of 18 years (1995–2012) for Envisat family and 26 years (1992–2017) for Jason family in order to be used in calibration of CERA-20C wave height. The mean wave period is also estimated from RA backscatter coefficients (Ku and C bands) and the significant wave height by using Artificial Neural Network Method. Then the estimated mean wave periods are used for the calibration of CERA-20C wave period. Calibrated CERA-20C data are compared with in-situ measurements for the verification purposes. Results of verification study show that the calibrated CERA-20C wave data agree well with the in-situ measurements in terms of Quantile-Quantile analysis with lower deviations from y = x line and capture the largest sea states. In fact, CERA-20C, century-based wave data become appropriate to determine the extreme waves to be used in the design of coastal structures along the Turkish coasts.